Psycho-Emotional Stability of the Individual in the Period of Societal Transformations - Yana Raievska; Svitlana Kulbida; Ruslan Lavlinskyy; Nazar Senytsia (Insight: the psychological dimensions of society, 2025)
The aim is to conduct theoretical and empirical research on the phenomenon of psycho-emotional stability in the period of societal transformations. Psycho-emotional stability is regarded as the dominant psycho-complex of the individual’s traits, abilities, and competencies to maintain efficient functioning through self-regulation of activities. Societal transformations are positioned as sociogenic challenges, including pandemics, military conflicts, climate disasters, societal upheavals, and social changes of various scales. Methods. The research involved students of three degree levels: “Bachelor”, “Master”, “Doctor of Philosophy”; academic staff, and employees of the Interregional Academy of Personnel Management (Ukraine) and Ivan Franko National University of Lviv (Ukraine); employees, middle managers, heads of departments, divisions, and structural subdivisions in the field of trade and production of the National Network of Shopping Centers “Epitsentr” (Ukraine) and Beauty Hypermarkets “Yeva” (Ukraine) with a total of n = 323 respondents aged 18 to 56 years. Valid and reliable psychodiagnostic tools were applied. Results. Respondents reported a medium level of the key research parameters. Pearson’s correlation analysis was used to establish two significant direct correlations between emotional stability and “independence/malleability” (p < .001) and “confidence” (p = .040). This confirms the direct dependence of emotional stability on the individual’s autonomy and assertiveness. Factor analysis revealed nine components with a total variance of Σd = 80.519%. Seven factor formations with significant loadings were interpreted: F1 “Resourceful psycho-emotional stability”, F2 “Safe psycho-emotional stability”, F3 “Adaptive psycho- emotional stability”, F4 “Independent psycho- emotional stability”, F5 “Psycho-emotional stability of guilt”, F6 “Open psycho-emotional stability”, and F8 “Intellectual psycho-emotional stability”. Discussion and Conclusions. It was substantiated that theoretical and empirical research is an attempt to clarify dominant psycho-complexes of the individual’s traits, abilities, and competencies that ensure a balance and efficient functioning through self-regulation of activities in the space of continuous societal transformations and in the dimensions of the individual’s dispositional readiness for change through implementing personal competencies and the ability to accept or not accept oneself and one’s life. The results obtained are valuable for those who offer individual and group psychological support in sociogemic situations.